Russian peasants and Soviet power. A study of collectivization. Transl. by I. Nove with the assistance of J. Riggart. With a pref. by A. Nove (Allen and Unwin, 1968)
With bibliogr. and index. Original title: La Paysannerie et le pouvoir soviétique.